Estimation of major genetic determinants of grain properties of selected Malaysian and Sri Lankan rice varieties - Banneka Mudiyanselage, Kumuduni Senarathne Menike (2022)
The world rice breeding programs aim at the improvement of the yield while enhancing grain quality to meet health aspects. Physical, physicochemical composition, antioxidant activities and molecular analysis of selected Malaysian and Sri Lankan improved rice varieties were conducted. Five Malaysian indica rice varieties namely, MARDI Siraj 297 (MS297), MR219, MR220, MR263, MR284 and twelve Sri Lankan rice varieties namely, Bg 252, Bg 300, At 311, Bg 94-1, Bg 352, Bg 358, Bg 359, At 362, Bw 367, Ld 368, At 405 and Bg 406 were employed in this study. The results found a significant difference in grain length and width where Bw 367 was the shortest (3.71 mm), and the longest was MS297 (7.36 mm). In terms of grain width, At 405 variety is the lowest (1.63 mm), and Bg 352 is the widest (2.31 mm). Significant differences in milling characteristics where the percentage of brown rice (%Br) is the highest in At 311 (80.8 %) and the lowest in Bg 252 (77.8 %), Bg 352 shows the highest %TMR value (75.5%), MR284 shows lowest (69.6%), and then %HG, Bg 358 shows the highest (73%), and the lowest is At 311 (58%). There were significant differences of apparent amylose contents (AAC) and gelatinization temperatures (GT) (ANOVA, p<0.05). All Malaysian rice varieties and At 311 had intermediate AAC meanwhile, other Sri Lankan rice varieties possessed high AAC. In addition, all Malaysian varieties, and Bg 300, Bg 359, Bw 367 and Ld 368 had intermediate GT levels, however, Bg 352, At 362, At 405, and Bg 406 showed low GT values. The antioxidant activities of total phenolic content (TPC), total flavonoid content (TFC), ferrous reduction potential (FRAP), and DPPH scavenging activity for both Malaysian and Sri Lankan rice varieties were conducted. Data analysis using ANOVA at p<0.05 with n=4 for antioxidant data while, multivariate analytical methods of Hierarchical cluster analysis (HCA), Principal components analysis (PCA), and Pearson correlations were performed using MINITAB window ver. 17. Results showed that there is significance difference observed (ANOVA, p<0.05) which is TPC range between 275 to 844 mgTAE100−1g, TFC range is 318 to 691 QE100−1g, and FRAP range is 0.23 to 1.34 mM100−1g, and DPPH range is 54.45 to 39.79 mg/mL. Red-pigmented rice which is Ld 368, At 362, Bg 252, At 311, and Bg 406 has high antioxidant activity, this is due to its higher phenolic and flavonoid content than white rice. HCA and PCA were used to classify the varieties into groups. There were four clusters in HCA at 55 similarity levels. In PCA analysis, the length, shape, TFC, and AAC are related to PC1 (37.6%) and the first four components explained 82.3% of the total variability. Pearson’s analysis showed strong correlations of pericarp-colour with antioxidant activities (TPC (r=0.86), TFC (r=0.84), FRAP (r=0.88), DPPH (r=0.76)). Furthermore, TFC with TPC (r=0.71), FRAP (r=0.76), and thousand-grain weight with length (r=0.63), while significant negative correlation showed length with TMR (r= (-0.61)) and HG% (r= (-0.80)). Genetically distant parents can be used as parental materials to have different genetic makeup. Identification of the presence of 'waxy' genes that encode amylose content, phylogenetic relationships based on 'waxy' gene sequences and genetic variation through SSR marker analysis for Malaysian and Sri Lankan rice varieties has been done. Fifteen micro satellite markers were evaluated. Molecular analysis was conducted by Bio Edit 7.2, NCBI Blast, ClustalW and MEGA- 11.0 software’s. The availability of a waxy gene encoding GBSS1 that determines amylose contents in selected rice varieties was confirmed. Two single nucleotide polymorphisms at A/C in Exon 6 at position 3911, and T/C in the splicing site of Intron 6 at position 3922 of the waxy gene were observed. All the selected varieties with high AAC were shown the sequence of ‘AGTTATA’ at the putative leader intron 5’ splice site. These indices can be used as molecular marker for differentiate amylose classes. Phylogenetic relationships were identified according to amplified sequences of Malaysian and Sri Lankan improved rice varieties. Six polymorphic micro satellite markers were identified and the most polymorphic ones were RM312, RM259, and RM202. Identified variations and relationships of selected Malaysian and Sri Lankan rice varieties can be utilized as important genetic sources for incorporating future rice breeding programs.